Phytoplankton chlorophyll-a biomass and the relationship with water quality in barrang caddi, spermonde, indonesia - Maslukah, Lilik; Setiawan, Riza Yuliratno; Nurdin, Nurjannah; Helmi, Muhammad; Widiaratih, Rikha (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
The investigation of spatial changes in phytoplankton biomass and turbidity provide essential information for the survival of the coral reef ecosystem. The phytoplankton biomass variations are driven by many factors, such as nutrient inputs from anthropogenic and natural. In turn, turbidity is determined by sediment resuspension or transport from terrestrial systems. The estimation of phytoplankton biomass is represented by the chlorophyll-a concentration. This study aimed to analyze the chlorophyll-a dynamics to water quality parameters, such as turbidity, suspended solids, dissolved oxygen, pH, salinity and temperature. The in-situ data gathered at 26 stations in the waters of the Barrang Caddi Island in August 2020. The results show that chlorophyll-a and turbidity have a negative correlation in the western and eastern regions, since turbidity inhibits the rate of photosynthesis and causes the decreasing of phytoplankton biomass. Nevertheless, the highest concentration of chlorophyll-a was found in the southern location, in small spots around islands and reefs, including near Barrang Caddi Island. Total Suspended Solid has more significant effect on chlorophyll-a than other water parameters, such as turbidity, temperature, salinity in the study area. © 2022, Polskie Towarzystwo Inzynierii Ekologicznej (PTIE). All rights reserved.